Do desmentido ao abandono: um estudo sobre o trauma a partir da teoria ferencziana - Ferrador, Amanda Barbosa (Universidade Federal de São Carlos, 2025)
The purpose of this essay is to weave a conceptual reading of trauma based on S. Ferenczi's theory, with a focus on disavowal and abandonment. To do this, a theoretical study was carried out with clinical case reports that considered ‘trauma in two stages’ so that it would be possible to differentiate between abandonment and disavowal. The first chapter looks at trauma in two stages, focusing on disavowal, and ends with a clinical case that illustrates this concept. The second chapter deals with traumatic abandonment. It uses two clinical cases that mobilise Ferenczi's theory to distinguish between disavowal and abandonment and, consequently, between “trauma in two stages” and “traumatic abandonment”. From this point of view, the author defends the thesis that abandonment is a type of trauma that can be identified in Ferenczi’s theory and that differs from the trauma of disavowal.

Le but de ce travail est de réaliser une lecture conceptuelle du traumatisme à partir de la théorie de S. Ferenczi, en mettant l'accent sur le déni et l'abandon. Pour ce faire, une étude théorique a été réalisée avec des cas cliniques qui ont envisagé le « traumatisme en deux temps » afin de pouvoir différencier l'abandon et le déni. Le premier chapitre aborde le traumatisme en deux temps, en se concentrant sur le déni, et se termine par un cas clinique qui illustre ce concept. Le deuxième chapitre traite de l'abandon traumatique. Il s'appuie sur deux cas cliniques qui mobilisent la théorie de Ferenczi pour faire la distinction entre déni et abandon et, par conséquent, entre « traumatisme en deux temps » et « abandon traumatique ». De ce point de vue, l'autrice défend la thèse selon laquelle l'abandon est un type de traumatisme identifiable dans la théorie ferenczienne et différent du traumatisme du déni.
From disavowal to abandonment: a study of trauma based on Ferenczi’s theory
Du déni à l'abandon : une étude du traumatisme selon la théorie ferenczienne
Keywords: Trauma; Abandono; Desmentido; S. Ferenczi; Abandonment; Disavowal; Traumatisme; Abandon; Déni; CIENCIAS HUMANAS::PSICOLOGIA